Free Radical Reactivity of a Phosphaalkene Explored Through Studies of Radical Isotopologues. Issue 1 (5th December 2018) - Chandrasena, Lalangi; Samedov, Kerim; McKenzie, Iain; Mozafari, Mina; West, Robert; Gates, Derek P.; Percival, Paul W.
Abstract: Muonium (Mu), an H atom analogue, is employed to probe the addition of free radicals to the P=C bond of a phosphaalkene. Specifically, two unprecedented muoniated free radicals, MesP . −CMu(Me)2 (1 a, minor product) and MesPMu−C . Me2 (1 b, major product), were detected by muon spin spectroscopy (μSR) when a solution of MesP=CMe2 (1 : Mes=2, 4, 6‐trimethylphenyl) was exposed to a beam of positive muons (μ + ). The μ + serves as a source of Mu (that is, Mu=μ + +e − ). To confirm the identity of the major product1 b, its spectral features were compared to its isotopologue, MesPH‐C . (Me)CH2 Mu (2 a ). Conveniently, 2 a is the sole product of the reaction of MesPH(CMe=CH2 ) (2 ) with Mu. For all observed radicals, muon, proton, and phosphorus hyperfine coupling constants were determined by μSR and compared to DFT‐calculated values. Abstract : Phosphaalkene and muonium get radical : Muonium, an H‐atom analogue, reacts with a phosphaalkene to form two radicals, a carbon‐centered radical (major product) and a phosphinyl (minor product). Muon, proton, and 31 P hyperfine coupling constants are reported for these radicals and an isotopologue generated from an alkene.